Ecological polyfunctionality of microorganisms and plant-microbial complexes in bioremediation of polluted soils - Kulikou, Yaroslav (Journal of the Belarusian State University. Ecology, 2024)
Mechanisms of biosorption and biodegradation of pollutants in the soil, associated with a number of physiological and biochemical characteristics of microorganisms and depending on their species diversity and specific action, are revealed. The role and importance of microorganisms is noted on the example of cyanobacteria, micromycetes and algae as effective soil bioremediators. A promising direction for improving the processes of bioremediation of soil ecosystems is the use of algalcyanobacterial communities. Cyanobacterial associations exhibit particular resistance to pollutants. They are able to adapt to oil, petroleum products, heavy metals, chemical weapons destruction products, maintain the oxidative level of ecosystems due to the release of oxygen, and increase the number of heterotrophic satellites in associations. Cyanobacterial biological preparations in combination with mineral fertilizers, when applied to oil-contaminated soils, activate oil degradation processes. In many respects, the degradation ability of cyanobacteria in relation to oil is explained by the fact that favorable conditions are created in the colonial mucus of cyanobacteria for the development of other microorganisms. It has been shown that the biosorption function of cyanobacteria is influenced by their population density, the degree of aggregation, the time of contact with the pollutant and its concentration. The optimal parameters of the status of cyanobacteria for their use as biosorbents have been revealed. Among the most important aspects of the associative interaction of actinomycetes with phytocenoses can be named such as the role of these microorganisms in regulating the number and composition of their microflora (control of phytopathogens) and increasing the ability of plants to withstand a variety of abiotic stresses, including drought, salinization, soil contamination with heavy metals and other xenobiotics. The largest group of bioactive secondary metabolites of actinomycetes are antibiotics with antibacterial, antifungal, antiprotozoal and antiviral activity. The antibiotics produced by them can be active in natural conditions and have significance in the fate of other microorganisms in the root zone of plants. The ability of actinomycetes to form antibiotics is based on the competitive relationships of microorganisms in their natural habitat.
Keywords: soil bioremediation; native microflora; degrading microorganisms; cyanobacteria; plant-actinomycete complexes; plant-microbial interactions